Abrupt and gradual drying-off procedure and intramammary dry treatment: Impact on udder health status of Chios breed dairy sheep - Sougaris, Savvas; Brozos, CN; Petridou, E; Papadopoulos, Th.; Kiossis, E (Journal of the Hellenic Veterinary Medical Society, 2022)
In order to evaluate the impact of drying-off procedure on udder health status and the effect of intramammary dry treatment on prevention of new intramammary infections and improving cure rate of mammary abnormalities, a randomized single blinded controlled trial was performed in which 80 Chios breed dairy ewes were randomly allocated into 2 groups. Ewes of Group A (n=40) dried off gradually during a 15-day period, whereas in ewes of Group B (n=40), udder drying-off took place abruptly. Half of the ewes of each group received intramammary infusion (1 syringe/teat) of benzathine cloxacilline (IDT subgroup, n=20). The rest of the ewes of each group received no treatment at all (control subgroup, n=20). Representative samples of teat duct material and milk were aseptically collected from each mammary half for cytological and microbiological examination. Samples were collected using both conventional and aseptic techniques at the time of enrollment until the final milking before dry off (7 to 14 days before the expected dry period), at dry period (approximately 65 days) and continued at lambing until the end of the ongoing milking period. 61.8% of bacterial isolates obtained from teat duct and milk were identified as coagulase-negative staphylococci (CNS). No significant differences were noticed between the two groups in the frequency of mammary gland infection peri-partum (p=0.466), in the risk of new mammary infections during dry period (p=0.750) and in the cure rate of any subsequent mammary infection (p=0.131). Drying-off procedure had no significant impact on somatic cell counts (p=0.760) or milk leucocyte subpopulations (p>0.05) but had a significant effect on milk production of the next lactation period (p<0.001). Ewes treated with antibiotic agent presented a significantly higher cure rate of subsequent mammary infections (p=0.036) and a significantly lower risk of new mammary infections (p=0.039) during dry period, compared to the control group. No statistically significant differences were noticed concerning the impact of treatment on cytological profiles (p>0.5), somatic cell counts (p=0.581) and milk production (p=0.705). The results strengthen the hypothesis that drying off procedure does not affect cure rate neither reduce the risk of new infections during dry period and has no effect on development of mastitis around dry period whereas the use of intramammary dry treatment provides a better bacteriological cure rate of the mammary gland and decreases the possibility of new intramammary infections during dry period.